The Policy Landscape of Sexual Orientation - Naylor, Lorenda (Journal of Public Management & Social Policy, 2013)
This paper examines the intersection of public administration and sexual orientation through a policy process framework that combines the stages model of policymaking and elements of the policy streams metaphor. Within this framework, we explore the emergence of sexual orientation as a policy issue, the extension of domestic partner benefits, and the battle over marriage equality in the legislative and judicial arenas of local, state, and federal government.
Keywords: Public Administration; Sexual Orientation; Policymaking; Marriage Equality